Synthesis, characterization, and crystal structure determination of palladacycles of para-substituted 2-thiobenzylazobenzenes - Bhattacharjee, Tirtha; Kalita, Mukul; Chakravarty, Debamitra K.; Barman, Pranjit; Puranik, Vedavati G. (Journal of Coordination Chemistry, 2014)
Bichelated neutral palladacycles (1-3), [Pd(L)Cl], were synthesized from reaction of the new potential tridentate (C,N,S) ligands, 2-thiobenzylazobenzene (L-1), 4'-methyl-2-thiobenzylazobenzene (L-2), and 4'-chloro-2-thiobenzylazobenzene (L-3) with sodium tetrachloropalladate(II), Na-2[PdCl4], in ethanol. The compounds were characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible, and thermogravimetric analysis. The crystal structures of L-2 and 1-3 were determined by single-crystal X-ray diffraction. In 1-3, the geometry around palladium remains almost square planar, coordinated to carbon, nitrogen, and sulfur of the ligand forming a bichelated cyclopalladate complex. The C-H center dot center dot center dot Cl type intermolecular hydrogen bonds, weak pi center dot center dot center dot pi, C-H center dot center dot center dot pi, and van der Waals interactions are believed to be the stabilizing forces for the crystal packing of these palladacycles.
Keywords: 2-Thiobenzylazobenzene; CNS-donor ligand; crystal structure; Palladacycles; Thermogravimetric analysis